2019
DOI: 10.1063/1.5110043
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties and stability of Ba3Cu16 − xSe11 − yTey

Abstract: Paper published as part of the special topic on Advanced Thermoelectrics Note: This paper is part of the special topic on Advanced Thermoelectrics. This paper was selected as Featured ARTICLES YOU MAY BE INTERESTED INA p-type thermoelectric material BaCu 4 S 3 with high electronic band degeneracy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This was an at least in part irreversible change, as the low-temperature data differed by a comparable amount; for example, at 323 K we found 357 and 390 Ω –1 cm –1 , respectively. Interestingly, both the next heating and cooling cycles resulted in lower numbers, for example, 422 and 439 Ω –1 cm –1 at 631 K. To investigate whether this irreversible behavior could be due to a change in the positions of the Cu + ions, as observed in the case of Ba 3 Cu 16– x Se 11– y Te y , single-crystal analyses were performed from both bars. The analyses showed no significant changes in the site occupancies of Cu and overall stoichiometry (Table ), and therefore we concluded that other irreversible material changes must have occurred, most likely caused by a hysteresis in the second phase transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was an at least in part irreversible change, as the low-temperature data differed by a comparable amount; for example, at 323 K we found 357 and 390 Ω –1 cm –1 , respectively. Interestingly, both the next heating and cooling cycles resulted in lower numbers, for example, 422 and 439 Ω –1 cm –1 at 631 K. To investigate whether this irreversible behavior could be due to a change in the positions of the Cu + ions, as observed in the case of Ba 3 Cu 16– x Se 11– y Te y , single-crystal analyses were performed from both bars. The analyses showed no significant changes in the site occupancies of Cu and overall stoichiometry (Table ), and therefore we concluded that other irreversible material changes must have occurred, most likely caused by a hysteresis in the second phase transition.…”
Section: Resultsmentioning
confidence: 99%
“…14−20 With such successes of the aforementioned compounds, the Kleinke group has looked into many Ba-containing copper chalcogenides such as Ba 6.76 Cu 2.42 Te 14 , 21 Ba 2 Cu 4−x Se y Te 5−y , 22 BaCuSiTe 3 , 23 and more recently Ba 3 Cu 16−x S 11−y Te y 24 and Ba 3 Cu 16−x Se 11−y Te y . 25 These materials exhibit recognizable copper chalcogenide attributes, such as Cu(S,Se,Te) 4 tetrahedral frameworks and p-type semiconductivity within a moderate temperature range, with zT values up to 0.9. 24 Previously our group published the crystal structure of Ba 3 Cu 14−δ Te 12 as well as the thermoelectric properties of its cold-pressed pellets.…”
Section: ■ Introductionmentioning
confidence: 99%
“…the reproducibility of the temperature-dependent changes of the Cu sites during heating and subsequent cooling. 66 Moreover,…”
Section: Discussionmentioning
confidence: 99%
“…the reproducibility of the temperature-dependent changes of the Cu sites during heating and subsequent cooling. 66 Moreover, Cu 1.4 Ag 0.4 Bi 5.4 Se 9 is less toxic than many other comparable thermoelectric materials due to the absence of elements like Pb.…”
Section: Discussionmentioning
confidence: 99%
“…Thermoelectric materials are assumed to be used at relatively high temperatures and their degradation mechanism has been investigated from the viewpoint of ionic conductivity. 115,116) The clarification of the degradation mechanism of thermoelectric materials assuming their use for IoT applications will be future work. In the search for new materials that will be important in the future, some cases of using materials for the search have been reported.…”
Section: Major Challenges and Thermophysical Metrologymentioning
confidence: 99%